1992
DOI: 10.30541/v31i4iipp.1111-1122
|View full text |Cite
|
Sign up to set email alerts
|

Why Most Development Projects Fail in Pakistan? A Plausible Explanation

Abstract: The need for effective .project planning in the farmework of macro planning has always been very strong in Pakistan as projects form the basis of development. Without the successful execution of projects, it is unlikely that development plans could be implemented effectively. In Pakistan an elaborate machinery for the planning of development projects exists but its prformance has been far from satisfactory. If one has to write the porject history of Pakistan, one wiII come a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…16 -18). Sahibzada and Mahmood (1992) have also stressed on the need of up gradation of human skills of the public sector managers in Pakistan. They report that most of the government officials have never attended training, while others need refresher courses.…”
Section: Project Management In Pakistanmentioning
confidence: 99%
“…16 -18). Sahibzada and Mahmood (1992) have also stressed on the need of up gradation of human skills of the public sector managers in Pakistan. They report that most of the government officials have never attended training, while others need refresher courses.…”
Section: Project Management In Pakistanmentioning
confidence: 99%
“…It comes as no surprise that planning/tracking/reporting is the first factor on their list because poor planning and bad project management, according to Saunders [21], remain major problems in project implementation. Numerous examples of development projects are reported to have failed in Pakistan due to the inefficient functioning of the machinery for planning development projects [2]. One of the most important reasons for project failure in Cameroun in particular, which may apply to many other parts of Africa is poor planning -most of the projects do not have a well-defined plan from outset [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agheneza [1] indicated that "Several development projects have failed to have a significant positive impact on the quality of life" in the Ngie, NW Province of Cameroon (page 74). Similarly, Sahibzada and Mahmood [2] reported that if one has to write the project history of Pakistan, one will come across numerous examples of projects that have failed due to the inefficient functioning of the machinery for planning development projects. Even when funds are available to carry projects through, some IDPs are considered failed operations and terminated by their donors after years of implementation, examples of which include Kpong Irrigation Project (KIP) in Ghana as well as Programme de Mise en Valeur des Plaines du Moyen-Bani (PMB) and Projet d'Amenagement du Perimetre Irrigue de Maninkoura (PAPIM), both of which are in Mali (see [3]).…”
Section: Introductionmentioning
confidence: 99%